THE EFFECT OF BUDGET PARTICIPATION ON THE ACCURACY OF PROFIT PLANNING: AN EMPIRICAL STUDY ON MSMES TYPICAL SOUVENIRS OF AMBON - Rita JD Atarwaman; Febriana Romauli Manurung; Nurhamna Rahmatulah; Chusnul Tehuayo (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to empirically analyze the influence of budget participation on the accuracy of profit planning in Micro, Small, and Medium Enterprises (MSMEs) that produce special Ambon souvenirs. The accuracy of profit planning is an important indicator of the success of MSME financial management, considering their limited resources and high levels of environmental uncertainty. This study adopts a quantitative approach using a survey method. Primary data was collected through a questionnaire distributed to 30 owners or managers of MSMEs for special Ambon souvenirs, which were selected using purposive sampling. Data analysis was carried out using descriptive statistics and simple linear regression analysis. The results of the study show that budget participation has a positive and significant effect on the accuracy of profit planning. These findings show that the higher the level of involvement of MSME actors in the budgeting process, the more accurate the profit planning will be. This research theoretically contributes to the development of managerial accounting in the context of MSMEs and provides practitioner implications for business practitioners and local governments in improving the quality of MSME financial management.